The Effect of CuO on the Thermal Behavior of the High-Energy Combustion Agent of the Al/MnO2 System - Hao Wang; Tao Guo; Wen Ding; Miao Yao; Xiang Fang; Jia-xing Song (Advances in Materials Science and Engineering)
In this work, the effect of CuO addition into the high-energy combustion agent of Al/MnO2 system was studied. First, the combustion experiments of five samples with different contents had been carried out, in which CuO was found capable of influencing the flame ejection to a great extent. Then, in order to find out the underlying reasons, CuO effects on the thermal behavior of Al/MnO2 system were analyzed via theoretical calculations of Gibbs free energy and enthalpy changes. In addition, field emission scanning electron microscopy (FE-SEM) that could characterize the mixture morphology and thermogravimetric-differential scanning calorimetry (TG-DSC) that could indentify the exothermic and endothermic reactions and measure mass change were carried out. Finally, on the basis of all experimental findings, it was suggested that addition of CuO into Al/MnO2 system could result in dramatic increase of gas content throughout the reaction and the consequent high pressure. Also, speed of flame injection and heat released in the high-temperature area would thus be conducive to the continuous exothermic behavior of the reaction.